Evaluation of correction rates for titanium-alloy and cobalt-chrome-alloy rods in adolescent idiopathic scoliosis - Chaudhary, Haresh F.; Soni, Manthan; Chaudhary, Kuldeep R. (International Journal of Research in Orthopaedics, 2021)
Background: The customary treatment of AIS is spinal fusion with instrumentation using rigid rods. In parallel, agents such as, curve magnitude, points of fixation, level instrument selection, curve flexibility, kind of anchor rods used for patients and post-operative care are the main factors affecting the outcome of surgery. Methods: A total 50 patients was included in the study. The control group, which included 31 patients treated with Ti rods, was compared with an experimental group of 19 patients treated with CCM rods. Correction surgery was performed through posterior approach using rod-rotation maneuver after inserting a pedicle screw in each vertebrae within the fusion. Six-millimeter CCM and six-millimeter Ti rods were used in experimental and control groups, respectively. Pre and postoperative indices of coronal alignment and sagittal alignment were measured. Results: There was no statistical difference between the two groups for age, sex, Risser’s stage, preoperative Cobb’s angle, type and flexibility of curvature. The correction rate of thoracic curve was 71.4±10.2% for the CCM group and 71.8±6.1% for the Ti group. There were no statistical differences between the two groups for all coronal and sagittal factors (p>0.05). Conclusions: AIS cases with double curvature, there was no statistically significant difference between Ti and CCM rods for coronal and sagittal plane correction rates. The derivations from biomechanical studies do not translate into clinical situations.